TEACHERS CAN MOTIVATE STUDENTS TO LEARN - Turaqulova Maftuna Abdurazzoq qizi; Shodiyeva Gulrukh Nazir qizi (Scholar Express Journals, 2021)
Teaching English as a foreign language for Iranian students are required from first grade of guidance school. I have taught English in guidance school high school pre-university and university. Many students do poorly on assignments or in participation because they do not understand what to do or why they should do it. As I faced these problems I asked myself how do I motivate my students to learn English. This article provides some strategies and ideas which increasing students desire to learn.
Keywords: Motivation, student learner high school foreign language